2022
DOI: 10.1021/acs.jpclett.2c01059
|View full text |Cite
|
Sign up to set email alerts
|

Rearranging the Phase Distribution of Quasi-2D Perovskite for Efficient and Narrow Emission Perovskite Light-Emitting Diodes

Abstract: Quasi-2D perovskite light-emitting diodes (PeLEDs) have attracted significant attention for their promising light-emitting applications. However, quasi-2D perovskite films typically consist of a broad phase distribution and small grains with a large surface area to volume ratio, leading to inferior color purities and higher defect densities. Herein, a bifunctional additive ((l)-tryptophan bromide, l-TrpBr) was introduced into a quasi-2D perovskite film. The CO moiety of l-TprBr formed hydrogen bonds with S-MB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 40 publications
(88 reference statements)
2
22
0
Order By: Relevance
“…For the BZA-and PEA-based films, PB peaks of n2 are quite strong compared with those of n3 and n4, indicating a high proportion of n = 2 phase and wide phase distributions. It has been reported that small-n phases usually suffer from nonradiative recombination induced by strong electronphonon coupling [40]. In contrast, the fraction of n = 2 phase is dramatically reduced in the PPA-and POEA-based films with a high fraction of large-n phases and relatively narrow phase distributions, which is beneficial for radiative recombination and energy funneling.…”
Section: Resultsmentioning
confidence: 98%
“…For the BZA-and PEA-based films, PB peaks of n2 are quite strong compared with those of n3 and n4, indicating a high proportion of n = 2 phase and wide phase distributions. It has been reported that small-n phases usually suffer from nonradiative recombination induced by strong electronphonon coupling [40]. In contrast, the fraction of n = 2 phase is dramatically reduced in the PPA-and POEA-based films with a high fraction of large-n phases and relatively narrow phase distributions, which is beneficial for radiative recombination and energy funneling.…”
Section: Resultsmentioning
confidence: 98%
“…On the one hand, such a blue shift can result from its passivation effects at the quasi-2D perovskite grain boundaries. 45 On the other hand, it correlates with the improved quantum well structure in the quasi-2D film arising from the suppression of the bulk phases, which is evident from the gradual decrease in the absorption band edge and the XRD results (discussed later). 46 The X-ray diffraction (XRD) patterns of these films were characterized as follows.…”
Section: Optoelectronic Properties Of Quasi-2d Perovskitesmentioning
confidence: 88%
“…[ 15 ] It is worth noting that poor phase purity with wide phase distribution can lead to color impurity, especially for quasi‐2D perovskite with mixed 2D–3D phases. [ 16 ] The small‐n phases ( n = 1, 2, and 3; where n represents the number of inorganic layers) with strong electron‐phonon coupling are dominated by non‐radiative recombination, which may cause homogeneous broadening of FWHM. [ 17 ] Therefore, low defect density and phase‐pure single‐crystal perovskites have the potential to achieve higher color purity.…”
Section: Introductionmentioning
confidence: 99%